The Mediating Role of Sustainability Reports on the Influence of Good Corporate Governance (GCG) and Profitability in Improving Company Sustainability Performance - decelina firdha amalia; Indri Kartika (Interdisciplinary Social Studies, 2025)
This study examines the role of sustainability reports in mediating the relationship between good corporate governance (GCG) and profitability on corporate sustainability performance. The independent variables in this study are GCG and profitability, with sustainability reports as the mediating variable, and sustainability performance as the dependent variable. The study population was companies included in the IDX30 index for the 2021–2024 period. The sample selection used a purposive sampling method with certain criteria, resulting in 115 observations. Data analysis was conducted using panel regression and the Sobel mediation test with the help of Stata software version 17. The results show that GCG has a significant positive effect on sustainability reports. Meanwhile, profitability has a significant negative effect on sustainability reports. Conversely, GCG has a significant negative effect on sustainability performance. Meanwhile, profitability has a significant positive effect on sustainability performance. Sustainability reports are proven to have no significant effect on sustainability performance. Sustainability reports also do not act as a mediator in the relationship between GCG and profitability on sustainability performance. For academics, the results of this study can serve as a reference in developing studies related to sustainability performance by adding variables and a wider sample coverage. For companies, these findings emphasize the importance of improving the quality and relevance of sustainability reports. The government can use these results to strengthen regulations related to sustainability reporting, while investors can consider GCG implementation and sustainability reporting in investment decisions.